Analisis Pengaruh Jumlah Penduduk, Penduduk Usia Sekolah dan Pertumbuhan Ekonomi Terhadap Pengangguran Di Provinsi Sumatera Utara - Azhar Apriandi; M Dwi Nanda Arindi (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this research is to find out how the effect of population size, school-age population and economic growth on unemployment. This research was conducted in the province of North Sumatra. The data analysis technique in this study is quantitative analysis. The source of data in this study is secondary data downloaded via www.bps.go.id, especially data on population, school-age population, economic growth and unemployment in the province of North Sumatra. The analysis used is the Statistical Package for the Social Sciences (SPSS). By population (X1), school-age population (X2), economic growth (X3), and unemployment (Y). The results showed that X1 had a negative and not significant effect on Y, X2 had a negative and not significant effect on Y. X3 had a negative and significant effect on Y. It has a negative effect, meaning that the increasing the X variable, the Y variable will decrease. 92.9% of the total population, school-age population and economic growth affect the unemployment rate in the province of North Sumatra and 7.1% are influenced by other variables that are not included in the study.